Serial murder - Holmes, Ronald M. (SAGE, 2010)
What is serial murder? -- Mass murder and spree murder : two types of multicides -- Serial murder -- Theories of serial murder -- The visionary serial killer -- The mission serial killer -- The hedonistic serial murderer : the lust killer -- The hedonistic serial murderer : the thrill killer -- The hedonistic serial killer : comfort type -- The power/control serial killer -- Female serial killers -- Serial killers in foreign countries -- Health care professionals and serial murder -- The victims of serial killers -- Problems and solutions in serial murder investigations